PREPARATION OF FUTURE KINDERGARTEN TEACHERS FOR PEDAGOGICAL CREATIVITY - Kosenko, Yuliya (Continuing Professional Education: Theory and Practice, 2019)
The current pre-school educational institutions of Ukraine expect a kindergarten teacher who is willing to work under the conditions of innovative changes which take place in the pre-school education. This educator should be willing to produce new ideas concerning the organization of the educational process. He / she should be ready to initiate and implement their own creative projects. The educator should be capable to show the skills of creative activity, to organize such a learning environment which will bring up a creative personality of a child revealing his / her artistic inclinations and abilities. It means that an educator should at the same time be a researcher with new pedagogical thinking. This educator should definitely have a certain pedagogical courage and be a humanist and an optimist in beliefs. She / he also should see the preschool childhood in all its uniqueness and the pre-school educational institution – in all its diversity of creative ways and forms of pedagogical interaction with children. It is this teacher who should be prepared at universities nowadays and the university should first of all use the possibilities of professional subjects to achieve this target. The article discusses a teaching and methodical support and organizational promotion of the study of the subject «Pedagogical creativity» as a means of professional training of students of the «Preschool education» specialty for their pedagogical creativity.